English Communication for International Teaching Assistants - Ma, Rui (Journal of International Students, 2014)
English Communication for International Teaching Assistants is at extbook written specifically for international teaching assistants (ITAs) working in a typical U.S. undergraduate classroom. An ITA might speak fluently in English with a clear pronunciation, yet the undergraduate students in an US classroom may still have difficulty understanding him or her. High English oral proficiency does not necessarily lead to an ITA’s communicative competence, which, according to Canale and Swain (1980), includes grammatical competence, sociolinguistic competence, and also strategic competence.